Mechanism of Carrier Transport at Low Temperatures in n-Type Beta-FeSi2/p-Type Si Heterojunctions Fabricated by Facing-Target Direct-Current Sputtering - N. Promros; M. Shaban; R. Baba; T. M. Mostafa; T. Yoshitake; M. Takahara (My University, 2015)
The fabrication of n-type β-FeSi 2 /p-type Si hetero junctions was accomplished by FTDC Sat a substrate temperature of 600°Cwithout post-annealing.Their currentvoltage characteristic curves were measured at low temperatures ranging from 300 K down to 50 K.In order to examine the mechanism of carrier transport in the hetero junctions using thermionic emission theory, the ideality factor was estimated from the slope of the linear part of forward lnJ-V characteristic curves.In the temperature range from 300 K down to 225 K, the ideality factor was 1.23 at 300 K and increased to 2.02 at 225 K.The ideality factor values 2 implied that the mechanism of carrier transport was governed by a recombination process.In the temperature range from 200 K down to 50 K, the ideality factor was 3.34 at 200 K and increased to 15.56at 50 K.Parameter A was calculated to be constant.The temperature dependent ideality factor, together with the constant value of parameter A, implied that the predominant mechanism of carrier transport was a trap-assisted multi-step tunneling process.At highly applied forward bias voltage, the mechanism of carrier transport was changed to a space charge limited current process.
Keywords: BETA (programming language); Semiconductor materials and interfaces